TARIFF AS A TOOL FOR FINANCING PUBLIC TRANSPORT IN CITIES - Magdalena ZIOŁO; Piotr NIEDZIELSKI (Scientific Journal of Silesian University of Technology. Series Transport)
The aim of the article is to present the role of public transport and its financing methods, with particular emphasis on the role of transport tariffs in Poland. Tariffs in collective transport, in addition to its financing functions, that is, covering the cost of services, are increasingly fulfilling the functions of shaping the desirability of public transport, thereby supporting the city's competitiveness as a whole, both in relation to its residents and people who have jobs in the city or are guests/tourists. The article hypothesises that third generation tariffs are financial tools that allow cities to manage local finance more effectively and affect the competitiveness and appeal of public transport. The research process used methods of critical analysis of literature, induction and deduction, logical inference and economic and financial analysis.